ENSO Diversity Regulation of the Impact of MJO on Extreme Snowfall Events in the Peruvian Andes - Sulca Jota, Juan Carlos (2025)
Extreme snowfall events (ESEs) in the Peruvian Andes (10°–18.4° S, > 4000 m) result in considerable economic losses. Despite their importance, how El Niño-Southern Oscillation (ENSO) diversity modulates the impact of the Madden–Julian Oscillation (MJO) on ESEs in the Peruvian Andes remains unexplored. Daily ERA5 reanalysis data from 1981 to 2018 were analysed. This study examines 16 ESEs. A bandpass filter with a 20–90-day range was applied to isolate the intraseasonal component of the daily anomalies. Additionally, time series data from the real-time multivariate MJO (RMM) index and Eastern and Central ENSO (E and C) indices were utilised. Composites were performed to describe the atmospheric circulation patterns related to ESEs in the Peruvian Andes under neutral, El Niño and La Niña conditions in the central and eastern Pacific Ocean. Under non-ENSO conditions, the MJO alone does not trigger ESEs in the Peruvian Andes during the DJF season. The absence of a well-organised convection system over the Peruvian Andes prevents ESEs. Conversely, during the JJA season, MJO Phases 5, 6 and 7 induce ESEs in the southern Peruvian Andes by enhancing moisture flux from the east through the equatorward propagation of an extratropical Rossby wave train that crosses South America and reaches the Altiplano region. In terms of ENSO diversity, the combined effects of the Central La Niña and MJO Phases 6 + 7 induce ESEs across the Western Cordillera of the southern Peruvian Andes during the DJF season. During austral winter, the interaction between the Central El Niño and MJO Phases 8 + 1, Eastern El Niño and MJO Phases 2 + 3, and Eastern La Niña and MJO Phases 8 + 1 induce ESEs across the Peruvian Andes.